The burden of angioedema on United States emergency departments: 2006–2010. (15th November 2016) - Smith, Aaron; Ray, Meredith; Jain, Nikhita; Zhang, Hongmei; Sebelik, Merry
Abstract : Objectives/Hypothesis: Angioedema (AE) is a condition that may prompt a visit to an emergency department (ED), and can quickly progress to airway obstruction. To optimize treatment of AE, it is necessary to understand epidemiology and practice patterns. This study measured the magnitude of AE ED visits and characterized demographics, management, frequency of airway interventions, and mortality. Study Design: Analysis of two national data sets. Methods: From the Nationwide Emergency Department Sample and National Hospital Ambulatory Medical Care Survey, we identified all patients presenting from 2006 to 2010 with a primary diagnosis of AE, characterized by the International Classification of Diseases, Ninth Edition, Clinical Modification code 995.1. The discharges were weighted and stratified by comorbidities, age, treatments, and region. χ 2, t test, and linear regression were employed for comparisons. Results: Total discharges increased from 87, 481 (29.3 of 100, 000 people) to 111, 116 (35.8 of 100, 000 people). More females were afflicted (57%), and 41.1% were African American. The majority (83%) of patients were discharged from the ED. Twelve percent of cases were attributed to antihypertensive adverse reaction, and these patients were older ( P < .0001, odds ratio [OR] = 1.02), and had more comorbidities ( P < .0001, OR = 5.66), hospital admissions ( P < .0001, OR = 4.83), and intubations ( P < .03, OR = 2.07). Overall, patients required intubation infrequently (<1%) and mortality was low (0.08%). Conclusions: The AE burden on EDs has increased over time. Patients with adverse reactions to antihypertensives are older, have more comorbidities, and require admission and intubation more frequently. Further investigation is needed to better delineate causation and outcome predictors, and to understand regional practice variance. Level of Evidence: 2c. Laryngoscope, 127:828–834, 2017